Field Test Investigation of the Pile Jacking Performance for Prefabricated Square Rigid-Drainage Piles in Saturated Silt Sandy Soils. (13th December 2019) - Wang, Xiangying
Abstract : The rigid-drainage pile, designed to accelerate the dissipation of excess pore water pressure around the pile, is a new type of pile that combines the bearing capacity of ordinary rigid piles and the draining capacity of gravel piles. Field tests of these new piles were performed for the first time at a construction site in the new campus of Jiangyin No. 1 High School. Numerous parameters were observed for the test piles in many trials, including the excess pore water pressures, horizontal soil pressures, and displacements. At the measuring position at 0.6 m from the pile center, the rigid-drainage pile dissipates 70% of the peak excess pore water pressure in 1000 s, whereas the ordinary pile requires nearly 4000 s to dissipate the identical amplitude. The field test results clearly demonstrate that the rigid-drainage pile can reduce the amplitude of the peak pressure caused by piling in the liquefiable layer, quickly dissipate the excess pore water pressure, reduce the loss of effective stress in the soil surrounding the pile, and maintain the foundation stability.